Role of mitochondria-associated endoplasmic reticulum membranes in insulin sensitivity, energy metabolism, and contraction of skeletal muscle - Nieblas, Bianca; Pérez-Treviño, Perla; García, Noemí (Frontiers in Molecular Biosciences, 2022)
Skeletal muscle has a critical role in the regulation of the energy balance of the organism, particularly, as the principal tissue responsible for insulin-stimulated glucose disposal and the major site of peripheral insulin resistance (IR), which may result in a reduced oxidative capacity of mitochondria, and endoplasmic reticulum (ER) stress. ER stress led to the accumulation of diacylglycerol and ceramides in the cytosol which inhibits insulin signaling. Those organelles form contact sites, known as mitochondria-associated ER membranes (MAMs). This interconnection seems to be involved in various cellular processes, including Ca2+ transport and energetic metabolism, therefore MAMs could play an important role in maintaining cellular homeostasis. Evidence suggests that alterations in MAMs may contribute to IR. However, the evidence does not refer to a specific subcellular location, which is of interest due skeletal muscle is constituted by oxidative and glycolytic fibers as well as different mitochondrial populations that appear to respond differently to stimuli and pathological conditions. In this review, we show the available evidence of possible differential responses in the formation of MAMs in skeletal muscle as well as its role in insulin signaling, and the beneficial effect could have in the regulation of energetic metabolism, and muscular contraction.